Marine Chemical Ecology - McClintock, James (CRC Press, 2009)
The interdisciplinary field of marine chemical ecology is an expanding and dynamic science. It is no surprise that the breadth of marine organisms studied expanded in concert with developments in underwater technology. With its up-to-date subject reviews by experts, Marine Chemical Ecology is the most current, comprehensive book on the subject. The book provides cellular, physiological, organismal, evolutionary, and applied perspectives creating a high-resolution snapshot of the field at the start of the 21st century.